2021
DOI: 10.1021/acs.chemrestox.0c00514
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics and Metabolomics Assessment Indicated Metabolic Alterations in Hypothalamus of Mice Exposed to Triclosan

Abstract: Triclosan (TCS) is a ubiquitous antimicrobial used in many daily consumer products. It has been reported to induce endocrine disrupting effects at low doses in mammals, disturbing sex hormone function and thyroid function. The hypothalamus plays a crucial role in the maintenance of neuroendocrine function and energy homeostasis. We speculated that the adverse effects of TCS might be related to the disturbance of metabolic processes in hypothalamus. The present study aimed at investigating the effects of TCS ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…1,2,35 Although the metabolic profiles disturbed by triclosan were different, it was found that triclosan significantly disrupted energy metabolism. 1,2,35 To obtain more unknown metabolic profiles, nontargeted metabolomics is used here, and future analysis of samples with authentic standards is needed to validate compound names and pathway information found in untargeted metabolomics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,35 Although the metabolic profiles disturbed by triclosan were different, it was found that triclosan significantly disrupted energy metabolism. 1,2,35 To obtain more unknown metabolic profiles, nontargeted metabolomics is used here, and future analysis of samples with authentic standards is needed to validate compound names and pathway information found in untargeted metabolomics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Overall, triclosan exposure disrupts macrophage metabolism by disrupting central carbon metabolism and purine metabolism. Untargeted metabolomics has also been used by other researchers to study the effects of triclosan on a variety of model organisms, such as hepatocytes, mouse hypothalamus, and zebrafish embryos. ,, Although the metabolic profiles disturbed by triclosan were different, it was found that triclosan significantly disrupted energy metabolism. ,, To obtain more unknown metabolic profiles, nontargeted metabolomics is used here, and future analysis of samples with authentic standards is needed to validate compound names and pathway information found in untargeted metabolomics.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in human ovarian granulosa cells in vitro showed that triclosan may increase estradiol and progesterone levels with upregulated expression of steroidogenesis gene ( Du et al, 2021 ) [E]. A study in mice exposed to triclosan for 13 weeks showed a decrease in body weight and metabolic alterations in the hypothalamus ( Huang et al, 2021 ) [E]. Using in vitro and gene-profiling assays, the estrogenic activity of triclosan was confirmed ( Yoon & Kwack, 2021 ) [E].…”
Section: Triclosan [Seda-37 276; Seda-39 212; Seda-40 292; Seda-41 25...mentioning
confidence: 99%